Twinning rate in the Health and Demographic Surveillance Systems (HDSSs) for Sub-Saharan Africa: Comparative descriptive analyses - (:unkn) unknown (My University, 2024)
Many studies of twin births in Sub-Saharan Africa show significant levels of twinning rates across the continent. The particularity of our study is to compare several local situations by analyzing data from 23 Health and Demographic Surveillance Systems (HDSSs). It calculates twinning rates in the Indepth network’s HDSSs and compares them with national twinning rates. This work also studies the variation of the twinning rate by maternal age, ethnicity, birth order and year of delivery. The results indicate a rate of twinning that varies greatly from one HDSS to another. The twinning rate of each HDSS is relatively close to the national twinning rate. In addition, we obtained some disparities in twinning rates according to the mother’s ethnicity, maternal age, birth order and year of delivery.
Keywords: African Research